Patch Testing and Prick Testing A Practical Guide Official Publication of the ICDRG - Lachapelle, Jean-Marie.; Maibach, Howard I.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Knowledge in the field of allergic contact dermatitis continues to expand rapidly owing to progress in the chemical, immunological, and clinical fields, including improved techniques of patch testing and prick testing. The third edition of this important book, which includes additional color illustrations, has been extensively revised, updated, and expanded to reflect the most recent developments. These include advances in patch testing methodology, in particular the new chambers that are appearing on the market, revision of the baseline series of patch tests to reflect the latest evidence-based work, and additional testing procedures. The result is a superb guide to the current management of positive and negative patch test and prick test reactions that will be invaluable for all practicing dermatologists, from the beginner to the well-trained expert.
The Spectrum of Diseases for Which Patch Testing -- Methodology of Patch Testing -- The Baseline Series of Patch Tests --  Photopatch Testing -- Additional Testing Procedures -- Clinical Relevance -- The True Test System -- The Spectrum -- The Methodology of Prick Testing -- Testing Procedures in Cutaneous Adverse Drug Reactions -- Conclusions.
Keywords: Dermatology; Allergy; Immunology; Occupational medicine; Dermatology; Allergology; Immunology; Occupational Medicine/Industrial Medicine